Frugivoría por aves en Phoradendron nervosum Oliv. (Santalaceae), un muérdago parásito de la ciudad de Loja - Mendoza Aguirre, Fátima Nathalí (2023)
Inter- and intraspecific relationships are important in the structure of biological communities. Relationships between organisms can form complex networks of interactions that allow us to study nature, visualize and describe ecological systems and mutualistic interactions such as seed dispersal, which plays an important role in determining the composition of plant communities. To date, little is known about the ecological benefits of introduced species in urban ecosystems. The frugivory between birds and plants was evaluated in sites where the mistletoe Phoradendron nervosum was found present, such as the Punzara and Jipiro sectors and the banks of the Zamora Huayco River. Sampling was carried out by means of 45-minute observations in each focal tree in the three selected sectors during four observation periods of three days each, and bird-plant interactions were recorded in April, May and June. In addition, the visitation and fruit removal rate of each of the identified bird species was estimated. Buthraupis montana, Euphonia cyanocephala, Euphonia xanthogaster, Pheucticus chrysogaster and Sicalis flaveola were identified as species that use this mistletoe as a food resource. Euphonia cyanocephala is the frugivorous bird that presented the highest rate of visits of 4.13 visits/45 minutes of observation, since this species feeds on wild fruits and coexists in urban areas, while Euphonia xanthogaster, despite having fewer visits than the previous one, presented the highest rate of fruit removal with 3.09 fruits/45 minutes. Thus, by knowing these interactions, it can be proved that Phoradendron nervosum is important in urban areas since they provide food resources, perching and shelter for various species of fauna, this information being an essential tool in the generation of strategies for the conservation of urban ecosystems. Key words: biological communities, ecological interactions, mucilage, fruit removal, zoochoria.